First report of alien Drosera rotundifolia in a high conservation value Patagonian peat bog. (15th October 2019) - Vidal‐Russell, R; Fernández Cánepa, G; Nuñez, C I; Ezcurra, C
Summary: Drosera L. (Droseraceae) is a genus of insectivorous plants distributed worldwide with 240 species, 40 of which are found in South America. In the temperate forests of Chile and Argentina the only species present is  D. uniflora . In a peat bog in Nahuel Huapi National Park, Argentina, a new species of Drosera was found in February 2018. To identify the species, we used morphological characters, and in addition, we sequenced two individuals for the nuclear region ITS and the chloroplast gene rbcL . Other Drosera sequences for these molecular regions were downloaded from GenBank, and a phylogenetic analysis was done to confirm the morphological identification of the Patagonian individuals. Morphologically and genetically, the species found in Nahuel Huapi is D. rotundifolia, a mostly Northern Hemisphere species. This is an alien species to the region and is thought to have been transported to the bog by tourists that visit the area. The presence of an exotic species represents a threat to this particular ecosystem with high conservation value. Currently, the National Park is taking control actions order to remove all individuals of the recently detected species. This study represents the first report of an alien species of Drosera in southern South America growing in the wild. This potentially invasive species may not only have negative impacts on the natural peat bog habitats in southern Argentina and Chile, but may also reach bogs in other temperate parts of the world.